Presence of the genus Glaresis Kolbe, 1905 in Sénégal and in Burkina Faso with the description of a new species (Coleoptera : Glaresidae) - (:unkn) unknown (My University, 2023)
Glaresis delaunayi n. sp. is described, representing the first record of the family Glaresidae from Senegal. The new species is compared to affine afrotropical species.
Keywords: African Research